Elderly Health Monitoring System based on IoT - Dzaky, Rafif; Dewi, Citra (Journal of Industrial Automation and Electrical Engineering, 2025)
The development of Internet of Things (IoT) technology has opened up great opportunities in improving the quality of health services, especially for the elderly who have a high risk of heart and respiratory disorders. This research aims to design and build an IoT-based elderly health monitoring system that is able to monitor three vital body parameters, namely heart rate and oxygen saturation (SpO₂) in real-time, and provide early warnings if abnormal conditions occur. This system uses MAX30102 sensors to measure heart rate and oxygen saturation. The NodeMCU ESP32 microcontroller is used as a data processing center connected to an I2C LCD for local display, buzzer as an alarm, and Blynk and Google Sheets applications for remote monitoring and data logging. The test results show that the system has a high accuracy rate, with an average accuracy of 98.88% for heart rate, 98.74% for oxygen saturation. The system is proven to work optimally and well integrated, making it feasible to be used as an independent and efficient elderly health monitoring tool.